Collaborative Learning Models and Their Effect on Student Engagement and Learning Outcomes - Hanik Ristiana; Dody Riswanto; Teofilus Ardian Hopeman; Deo Renaldi Saputra; Fu'ad Sholikhi (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study examined the effects of structured collaborative learning on student engagement and learning outcomes in secondary education using an empirical quasi-experimental design with a non-equivalent control group. Participants were purposively recruited from one school and allocated at the class level to either an experimental group receiving cooperative learning with defined roles, peer-regulation prompts, and task interdependence, or a comparison group receiving teacher-directed instruction. Data were collected through standardized pre-test and post-test achievement measures, structured classroom observations, and a multidimensional engagement questionnaire assessing behavioral, emotional, and cognitive engagement. ANCOVA results indicated that the experimental group achieved significantly higher adjusted post-test scores after controlling for baseline differences. Engagement analyses showed greater gains across all engagement dimensions in the experimental condition, with the strongest improvement in cognitive engagement. Regression-based modeling revealed that cognitive engagement was the most powerful predictor of post-test achievement, followed by behavioral engagement, while emotional engagement showed a weaker direct association under statistical control. The findings demonstrate that structured collaboration enhances learning by strengthening metacognitive regulation and sustained cognitive investment.